2016
DOI: 10.1111/jmft.12183
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Attunement in Therapy With Mexican‐Heritage Couples: A Grounded Theory Analysis of Client and Therapist Experience

Abstract: There is a need for culturally attuned approaches for couple therapy with Mexican/Mexican-Americans. This qualitative grounded theory study utilized interviews with 11 client couples of Mexican heritage and 14 marital and family therapists to shed light on how Latino and non-Latino therapists co-construct positive experiences of cultural attunement with Mexican and Mexican-American couple clients. Analysis identified a model of cultural connection through personal engagement with four interrelated phases: (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…A ttunement goes beyond raised social consciousness and conceptual understanding to include openness to take in the experience of others and respond sensitively to it (e.g., D'Aniello et al., ; Elias‐Juarez & Knudson‐Martin, ; Pandit, ChenFeng, & Kang, ). Socioculturally attuned practice recognizes inequitable social structures and resources while seeking to apprehend each client's unique confluence of social identities and being aware that identities and power positions are fluid across time and place as well as influenced by historical legacies of injustice (Boszormenyi‐Nagy & Spark, ; Brave Heart & DeBruyn, ; Monk, Winslade, & Sinclair, ; Watson, ).…”
Section: Socioculturally Attuned Practicementioning
confidence: 99%
“…A ttunement goes beyond raised social consciousness and conceptual understanding to include openness to take in the experience of others and respond sensitively to it (e.g., D'Aniello et al., ; Elias‐Juarez & Knudson‐Martin, ; Pandit, ChenFeng, & Kang, ). Socioculturally attuned practice recognizes inequitable social structures and resources while seeking to apprehend each client's unique confluence of social identities and being aware that identities and power positions are fluid across time and place as well as influenced by historical legacies of injustice (Boszormenyi‐Nagy & Spark, ; Brave Heart & DeBruyn, ; Monk, Winslade, & Sinclair, ; Watson, ).…”
Section: Socioculturally Attuned Practicementioning
confidence: 99%
“…Despite the continued stigma, for many who desire services, their greatest barrier is finding competent bilingual therapists (Rios‐Ellis et al., ). In fact, Elias‐Juarez and Knudson‐Martin () stated that Latinos in their study indicated that they had an increased sense of safety and openness when they had a bilingual therapist who spoke in Spanish. Moreover, clients who primarily or solely speak Spanish have historically struggled with a lack of social support, engage in shorter periods of treatment, and have higher termination rates (Kouyoumdjian, Zamboanga, & Hansen, ).…”
Section: Our Community Contextmentioning
confidence: 97%
“…As a consequence, many use the terms “Latin@” which is pronounced Latin‐ow (Wallerstein, ) and Latinx to decenter gender from the Latina/o term and to be more inclusive of gender diversity and lastly, (f) We use the term non‐English speaking Latinos to represent primarily Spanish speaking, immigrant Latinos in our community who do not speak English, however, we acknowledge that many Latinos do not speak Spanish, but speak Portuguese, sign language, or indigenous languages as their primary language. Overall, language is important in psychotherapy and continues to be a significant barrier for Latinos seeking and obtaining services (Elias‐Juarez & Knudson‐Martin, ).…”
Section: Our Community Contextmentioning
confidence: 99%
“…Außerdem werden wahrgenommene Sprachbarrieren oder die "kulturelle" Verschiedenheit von Psychotherapeuten als Gründe genannt, Patienten mit Migrationshintergrund für eine Behandlung abzulehnen (Mösko et al 2013). Eine authentische psychotherapeutische Beziehung, ein kritischer Umgang mit eigenen Stereotypen sowie die Fähigkeit, mit Nicht-Wissen umzugehen, werden von Psychotherapeuten als hilfreich eingeschätzt (Elias-Juarez und Knudson-Martin 2017;Niño et al 2016).…”
Section: Haltungs-und Einstellungsansatzunclassified